معوقات البحث العلمي فى كليات السياحة والفنادق: دراسة حالة على كلية السياحة والفنادق جامعة المنصورة - زهرى محمد عبدالفتاح (Finance and Business Economies Review, 2018)
Scientific research in institutions of higher education requires a clear scientific strategy and applicable and before that a supportive political administration. Its believes in the importance of scientific research in the progress and development of countries and societies, it also needs qualified academic and academic departments and is carried out by creative scientists in their fields, aware of the conditions of their countries and their needs, they are able to investigate everything that is new and ask questions and receive answers. The observer for the status of scientific research in Egypt notes that there are many obstacles and difficulties that hinder scientific research and limit its performance to its expected role which led to the delay of the process of development and progress. The study aimed at studying the obstacles of scientific research in the Faculty of Tourism and Hotels. To achieve this goal, 100 survey forms were distributed on the sample of the research and 88 forms were analyzed by using Spss program, The results found that the university did not allocate budgets to carry out scientific research in appropriate ways, Lack of cooperation from the staff in the institutions assigned to the field part for fear of being questioned if they cooperated with the researcher without the approval of their supervisors in the work, the supervisor does not have sufficient time to supervise and follow up the thesis. The research recommends activating the role of libraries in faculties and equipping them with an internet network connected to the global data network to facilitate researchers in obtaining periodicals and scientific researches, as well as the need to contain the number of conferences and scientific meetings, electronically and Paper to facilitate the follow-up of